Preliminary Survey on Population and Daily Activity Pattern of Long-Tailed Macaque (Macaca fascicularis) in Tanjung Datu National Park, Sarawak - Arifin, Ainaa Syazana; Mohd-Ridwan, Abdul Rahman; Challen, Belinda Carey; Nur-Aizatul, Tukiman; Noor-Faezah, Mohammad; Tingga, Roberta Chaya Tawie; Md-Zain, Badrul Munir (Malaysian Applied Biology, 2026)
Long-tailed macaques (Macaca fascicularis) are an endangered species that are facing increasing threats due to habitat fragmentation and limited foraging grounds. Thus, their extensive range of behaviours requires attention from research and management perspectives for their conservation. Studying the behaviour of the M. fascicularis population in Tanjung Datu National Park (TDNP), Sarawak, one of the smallest protected areas that is rich in biodiversity, is crucial for ensuring their conservation success. The purpose of this study was to examine the demographic and behavioural ecology of the long-tailed macaques in TDNP, as there is currently insufficient information available on the M. fascicularis population in the protected area. A population estimation study was conducted using a census walk from February 23rd to March 1st, 2024. The behaviour of M. fascicularis was observed using the scan sampling method during this period. The study was conducted within an area of around 11,222 m², with a total of 181 individuals recorded from two groups. Group A (175 individuals) was recorded near the HQ area, while Group B (6 individuals) was recorded in Telok Upas. No solitary individuals were observed during the study, and due to the direct count method, no variance estimate was calculated. Present results indicated that long-tailed macaques spent most of their time moving (53.79%), followed by resting (14.48%), feeding (13.44%), other activity category (7.93%), vocalisation (5.52%) and grooming (4.83%). Data from the population census and behaviour of the long-tailed macaques can help the park's management in prioritising habitat protection areas and monitoring the population trends for effective long-term conservation of the species within TDNP.